UTILIZING SHORT STORIES TO IMPROVE VOCABULARY OF 8th GRADERS JUNIOR HIGH SCHOOL - Widyasari, Fara Hanindita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study was conducted to analyze the use of English short stories to improve the vocabulary mastery of 8th grade students at a public junior high school in Surabaya and their perceptions towards the use of English short stories. The researcher used the Classroom Action Research (CAR) method, involving 28 students (13 males, 15 females) with varying abilities. Data was collected through tests and interviews related to the use of English short stories. According to the analysis, this study revealed that English short stories helped students improve their vocabulary skills (Mean: 68 > 72 > 80). Moreover, the students also had a positive perception of the use of English short stories.